Penerapan Metode Kisah dalam Penanaman Akhlak Mulia Peserta Didik Kelas V SD - Gabena Yolanda Nasution (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2024)
A lack of discipline in certain children was the impetus for the study, which found that instructors and classmates were not greeted with sufficient morality. Of all the learning strategies, the fourth grade teacher at SD Negeri 200119 Batang Ayumi Julu, Padangsidimpuan City uses a narrative approach in Islamic Religious Education (PAI) to help students develop high morals. The questions asked in this research are how to use narrative techniques to help children develop high moral standards and what those standards should look like. The purpose of this research is to ascertain the moral picture of students and learn how to use narrative techniques to influence students' moral development. A qualitative descriptive research design was used. Interviews and observations function as data collection tools. Reducing data, presenting data, and drawing conclusions are components of data analysis. Three methods were used to assess the validity of the data: triangulation, time extension, and persistence of observation. The findings of this research, accompanied by the use of narrative techniques with appropriate planning, implementation and assessment procedures, will form students' high moral standards towards Allah SWT, their teachers and other students.